1998
DOI: 10.1046/j.1365-2362.1998.00393.x
|View full text |Cite
|
Sign up to set email alerts
|

Scopolamine model of dementia: electroencephalogram findings and cognitive performance

Abstract: Background Memory and cognitive functions are known to decline with advancing age. Studies have suggested that this may be due to a decrease in cholinergic function in the brains of elderly people. This review aims to assess studies documented in the literature dealing with the 'scopolamine model' of dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
173
0
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 332 publications
(185 citation statements)
references
References 67 publications
9
173
0
3
Order By: Relevance
“…For example topically applied scopolamine to exposed feline cortex lead to the development of seizures but was prevented by application of the acetylcholinesterase inhibitor physostigmine (Tan et al, 1978). Systemic administration of scopolamine to healthy humans induces impairment to attentional processes, and memory, as well as decreases in higher frequency gamma/beta EEG power relative to lower frequency delta/theta power (Ebert and Kirch, 1998). Although not directly demonstrated in the current study, VNS has been shown to excite the nucleus basalis (NB) (Detari et al, 1983) and similarly to VNS, NB activation promotes arousal, suppresses seizure activity Berdiev et al, 2007), and promotes neural plasticity (Edeline et al, 1993;Engineer et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For example topically applied scopolamine to exposed feline cortex lead to the development of seizures but was prevented by application of the acetylcholinesterase inhibitor physostigmine (Tan et al, 1978). Systemic administration of scopolamine to healthy humans induces impairment to attentional processes, and memory, as well as decreases in higher frequency gamma/beta EEG power relative to lower frequency delta/theta power (Ebert and Kirch, 1998). Although not directly demonstrated in the current study, VNS has been shown to excite the nucleus basalis (NB) (Detari et al, 1983) and similarly to VNS, NB activation promotes arousal, suppresses seizure activity Berdiev et al, 2007), and promotes neural plasticity (Edeline et al, 1993;Engineer et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Scopolamine-induced memory impairment was suggested for modeling some features of geriatric memory dysfunction and of Alzheimer's disease (AD) memory impairment (Bartus, Dean, Beer, & Lippa, 1982;Ebert & Kirch, 1998;Giacobini, 1990). This was proposed because a mild cholinergic dysfunction occurs in the elderly and at early stages of AD.…”
Section: Discussionmentioning
confidence: 99%
“…Blockade of muscarinic acetylcholine receptors (mAChRs) has been shown to induce memory and attentional deficits in both animals and humans (Blokland, 1995;Ebert and Kirch, 1998;Everitt and Robbins, 1997;Green et al, 2005). Two of the cholinergic projections from the BF, those to the entorhinal cortex (EC) and the basolateral amygdala (BLA), have been shown to mediate distinct cognitive processes through mAChRs (Hasselmo, 2006;Hasselmo and McGaughy, 2004;Ingles et al, 1993;Power, 2004).…”
Section: Introductionmentioning
confidence: 99%